Finding meaning in translation; A.L. Becker’s “text coherence” - Hunter, Thomas M. (Wacana, Journal of the Humanities of Indonesia, 2020)
In this article I look at two closely related examples of A.L. Becker’s work on textual coherence and how they can be used as tools for finding meaning in translation. In the first example I draw on Becker and Oka’s work on deixis in Old Javanese (1974) to elucidate the subtle shifts of spatial and temporal reference in “Sītā’s Letter”, an innovative episode in the Old Javanese Rāmāyaṇa (OJR 11.18- 34). In the second example, I look at Becker’s analysis of the role of Indonesian verbal markers in his essay “The figure a sentence makes; An interpretation of a Classical Malay sentence” (1979b). I take these suggestions as a starting point to examine how shifts in the choice of active or passive verbal form establish contrasts in perspective in an Indonesian short story. My aim is to illustrate Becker’s dictum that we should look within languages and cultural systems for the elements of structure that give them coherence, rather than imposing theoretical models that may obscure rather than illuminate the objects of study.